1623 Atrial Fibrillation Post Aortic Valve Replacement: Prevalence and Causative Factors. (12th October 2021) - Baker, S; Badran, A; Naseer, M; Ohri, S
Abstract: Aim: Atrial fibrillation (AF) is the most prevalent arrhythmia. Post-Operative AF (POAF) occurs in a third of patients post cardiac surgery. We aim to explore the incidence of AF post aortic valve replacement (AVR) and whether clinical and echocardiographic parameters can predict the likelihood of AF and therefore influence the management of patients. Method: Our study consisted of 985 patients who underwent AVR between 2018 – 2019 from a single major cardiothoracic surgery centre in the UK. Data was collected from the electronic patient records retrospectively. Results: Mean age of the cohort was 71.8 years (27-92). There were more males (68.2%, n = 672) than females (31.8%, n = 313). A majority of patients (51.8%, n = 510) developed an episode of AF in the post-operative period, of which 65.1% was new onset (n = 330). Incidence of post-operative AF was associated with more HTN (p = 0.007), poor left ventricular function as well as increased left atrial diameter (P = <0.001). Conclusions: There is a high incidence of AF following AVR surgery. Comorbidities as well as left atrial diameter have a statistically significant relationship with this incidence and could be used as predictors of postoperative atrial fibrillation.